2019
DOI: 10.4314/gjds.v16i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of indigenous conflict management mechanisms: evidence from Bunkpurugu-Yunyoo and Central Gonja Districts of Northern Region, Ghana

Abstract: The Northern Region is witnessing protracted and relapsed conflicts, and attempts at resolving these largely through Western models, particularly the formal court system have not been successful. As such, this study explores the relevance of indigenous conflict management mechanisms in restoring enduring peace in the Northern Region of Ghana. The study employed a multiple case study design. Data was collected from fortythree purposively selected respondents using interviews, focus group discussions, and observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…These systems ensure the impartiality of third parties, provide transparency and accountability in procedures, and provide accessibility and speed in providing results. This concurs with Kwesi (2013) and Ibrahim et al's (2019) claim that parties to a conflict are urged to take an integrative (win‐win) strategy when conflict management techniques recognized the people's culture. That is, instead of using an adversarial, loser‐take‐all approach to conflict resolution, they adopt inquisitorial and restorative approaches.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These systems ensure the impartiality of third parties, provide transparency and accountability in procedures, and provide accessibility and speed in providing results. This concurs with Kwesi (2013) and Ibrahim et al's (2019) claim that parties to a conflict are urged to take an integrative (win‐win) strategy when conflict management techniques recognized the people's culture. That is, instead of using an adversarial, loser‐take‐all approach to conflict resolution, they adopt inquisitorial and restorative approaches.…”
Section: Discussionsupporting
confidence: 83%
“…The study recommended that cultural issues be adequately understood and addressed to avoid undermining peace negotiations. Similarly, Ibrahim et al (2019) explored the relevance of indigenous conflict management mechanisms in restoring enduring peace in the Northern Region of Ghana. Using Bunkpurugu‐Yunyoo and Central Gonja as the study districts, the results revealed that indigenous mechanisms based on the people's culture have features of inclusive, participatory approach at all levels of the conflict, which led to acceptable outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Goody (2018) believes this created the current stalemate in the Bole traditional area. Ibrahim et al (2019) observed that the modern history of Gonja has had no records of disagreement about who becomes the Yagbonwura. Succession disputes are rather pervasive at the divisional and sub-divisional levels ((GTC, 2019)).…”
Section: Introductionmentioning
confidence: 99%